The American History Videodisc - Schulz, Master Guide - Mugleston, William (Teaching History: A Journal of Methods, 1994)
Technological supplements for classroom use are becoming increasingly common. The American History Videodisc (ARV) is one of the most recent and attractive. It consists of 2490 still images and 68 motion sequences, organized into ten sections chronologically. The stills cover the sweep of United States history from prehistory to 1992. The motion sequences begin in the Progressive and World War I eras and go to the Gulf War.